Theory of Multiple Intelligence among Middle School Students - V, Gayathri; Kumar, Y Stanly Selva (Journal of Advanced Research in English & Education, 2022)
The purpose of the case study on “ Theory of Multiple Intelligence” was to map the dominant intelligences among the students attending school in the centre of the country, in order to enhance school teaching. First, we decided to examine the population of learners among seventh graders. Students’ age was selected based on the school needs . A case study was conducted in a middle school in Israel and included 158 students of different achievement levels and different backgrounds. The theoretical components of MI theory as proposed by Gardner (1983, 1999, 2004) and their implications for curriculum in the classroom were used to inform this study. Gardner is a professor of education at Harvard University whose groundbreaking research in psychology and human cognition helped him develop a theory that we each have distinct intellectual abilities that we demonstrate with unique aptitudes. The nine multiple intelligences: Verbal-linguistic: demonstrates strong verbal communication, advanced vocabulary, etc. Logical-mathematical:  understands logical and numerical patterns as well as abstract concepts. Spatial-visual: visualizes accurately and uses abstract information to picture the information in one’s head. Bodily-kinaesthetic: skilfully uses and controls the body and objects. Musical: produces rhythm and pitch and appreciates musical values. Interpersonal: responds appropriately to others by understanding social cues, motivations and moods. Intrapersonal: aware of one’s own feelings, values and thinking processes. Naturalist: identifies and categorizes animals, plants and other aspects of nature. Existential: contemplates deep questions about human existence, including the purpose of life, how we came to be, etc. How to cite this article:  Gayatri V, Kumar YSS. Theory of Multiple Intelligence among Middle School Students. J Adv Res Eng & Edu 2022; 7(1): 8-10. DOI: https://doi.org/10.24321/2456.4370.202212